2001
DOI: 10.1038/sj.bmt.1703305
|View full text |Cite
|
Sign up to set email alerts
|

A patient with anaphylactoid hypersensitivity to intravenous cyclosporine and subcutaneous phytonadione (vitamin K1)

Abstract: Bone Marrow Transplantation sis. There were several autoantibody positive patients who had never had acute or chronic GVHD.Furthermore, in a large study on long-term transplanted patients, 36% had a Karnofsky index Ͻ100% but only a few of them had active cGVHD. 7 This fits with earlier reports that the occurrence of autoantibodies after HSCT does not correlate with cGVHD but might be rather the expression of an abnormal B cell and/or T cell reconstitution. [3][4][5][8][9][10] Therefore, we hypothesize that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Some reports have classified these adverse reactions as anaphylactoid reactions [10]. Riegert-Johnson has reported one case of an adverse reaction to VK 1 and concluded that this patient most likely experienced an anaphylactoid (non-IgE-mediated) hypersensitivity reaction [11]. Fiore has defined “anaphylactoid” as an adverse drug event in which at least one of the reported adverse drug reactions includes any of the following CONSTART entries: anaphylaxis, allergic reaction, apnea, death, cardiac arrest, hypotension, shock or vasodilation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have classified these adverse reactions as anaphylactoid reactions [10]. Riegert-Johnson has reported one case of an adverse reaction to VK 1 and concluded that this patient most likely experienced an anaphylactoid (non-IgE-mediated) hypersensitivity reaction [11]. Fiore has defined “anaphylactoid” as an adverse drug event in which at least one of the reported adverse drug reactions includes any of the following CONSTART entries: anaphylaxis, allergic reaction, apnea, death, cardiac arrest, hypotension, shock or vasodilation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the number of severe adverse reactions caused by the intravenous administration of VK 1 has increased and attracted public attention (Fiore et al ., ; Riegert‐Johnson et al ., ). Because VK 1 is a lipid‐soluble substance and is poorly soluble in water, a solubilizer, such as Tween 80, is required to prepare it for injection (Qiu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…18,26 Of the 10 reactions detailing previous vitamin K1 exposure, 6 had previously received some form of vitamin K1. 25,26,29,30,32 Two cases reported on patients with prior reactions to other medications formulated with PEO-CO. 19,22 Five cases described rechallenge of the patient with vitamin K1 22,23,25,31,32 , 2 of which resulted in recurrence of the reaction. 23,25 Three pediatric patients ranging from newborn to 9 years of age were represented in the case reports ( Table 2).…”
mentioning
confidence: 99%